Power Efficiency Improvements through Peak-to-Average Power Ratio Reduction and Power Amplifier Linearization. (4th February 2007) - Chen Chen, Ning Ning; Zhou Zhou, G. Tong G. Tong; Qian Qian, Hua Hua
Abstract : Many modern communication signal formats, such as orthogonal frequency-division multiplexing (OFDM) and code-division multiple access (CDMA), have high peak-to-average power ratios (PARs). A signal with a high PAR not only is vulnerable in the presence of nonlinear components such as power amplifiers (PAs), but also leads to low transmission power efficiency. Selected mapping (SLM) and clipping are well-known PAR reduction techniques. We propose to combine SLM with threshold clipping and digital baseband predistortion to improve the overall efficiency of the transmission system. Testbed experiments demonstrate the effectiveness of the proposed approach.